PERAN MODERASI SUBJECTIVE NORMS PADA HUBUNGAN ATTITUDE DAN INTENTION TO SHARE KNOWLEDGE DALAM SISTEM PENGELOLAAN SDM PERGURUAN TINGGI - Eugenius Tejo Sukmojati Kristianto; Adi Santoso; Mariah Rabiatul Qibtiyah (JURNAL ILMIAH EDUNOMIKA, 2026)
This study aims to analyze the effects of extrinsic reward, social trust, sense of self-worth, and expected association on attitude toward knowledge sharing, as well as to examine the moderating role of subjective norms on the relationship between attitude and intention to share knowledge. The study employs a quantitative approach by distributing questionnaires to 80 non-academic staff members and analyzes the data using multiple regression and moderated regression analysis (MRA). The results show that sense of self-worth and expected association have a significant effect on attitude toward knowledge sharing, whereas extrinsic reward and social trust do not exhibit significant effects. Attitude toward knowledge sharing is proven to have a significant effect on intention to share knowledge. In addition, subjective norms act as a moderating variable that strengthens the influence of attitude on intention. These findings confirm that psychological and relational factors have a stronger contribution than external incentives in shaping knowledge-sharing behavior. Theoretically, this study enriches the development of the Theory of Reasoned Action (TRA) in the context of knowledge management in higher education. From a managerial perspective, this study recommends that organizations prioritize the strengthening of individual competencies, enhancement of psychological rewards, and facilitation of a collaborative culture supported by social support and leadership that fosters habitual knowledge sharing.